Caracterização e geocronologia de sequências turbidíticas no leste do greenstone belt Rio das Velhas, Quadrilátero Ferrífero, Brasil - Gabriel Oliveira Sepulveda (2020)
The Quadrilátero Ferrífero (QF) is an important, polydeformed mineral province, located in the southernmost portion of São Francisco Craton. Ancient sedimentary sequences are present within the meta-volcano-sedimentary Rio das Velhas greenstone belt (RVGB). The Córrego do Sítio unit (CdS), the most widely distributed sedimentary sequence of the RVGB, is part of the resedimented lithofacies association and hosts an important gold deposit. The identified sedimentary structures led the interpretation of these sequences as distal turbidites, corresponding to Tc and Te facies of the classic Bouma Sequence, deposited by turbidity current mechanism. But those features also allowed the interpretation of a bottom currents seting for Córrego do Sítio unit. Geocronological data pointed the main influence of the Rio das Velhas II magmatic event in the deposition of the eastern QF metasedimentary sequence, as evidenced by the maximum depositional age at 2818 ± 31 Ma. The surrounding metamorphic complexes terrains may acted as source areas during the deposition of the sedimentary sequences, probably in a convergent to collisional marginal tectonic setting (subduction stage).